2016
DOI: 10.4236/jbise.2016.98033
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Age and Duration of Cochlear Implant in a Congenital Deaf Population: An ERP Study

Abstract: Objective: It is well known that patients with Cochlear Implant (CI) have a large inter-individual variability in linguistic and auditory performances. This can be related to individual auditory processing abilities and integrity of auditory system from auditory nerve to cerebral cortex. P300 can be used for the evaluation of central auditory functions in people with hearing loss and CI. No studies considered the P300 in the population of prelingually deafened adults that underwent CI in old age. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…1), while the P300-N100 and the N200-N100 inter-peak latencies did not differ significantly between patients and controls. This means that the difference in N200 and P300 latencies found between patients and controls is due mainly to the N100 latency lag (of about 25-30 msec) in the patient group, a finding previously reported by Ghiselli et al 20 . Using LORETA on magnetoencephalographic data, Larson 28 found that the cortical generators of N100, elicited by the oddball paradigm, were located in the Heschl's gyrus, where previous studies identified the tonotopic map of the human auditory cortex (for an exhaustive review, see Saenz 29 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…1), while the P300-N100 and the N200-N100 inter-peak latencies did not differ significantly between patients and controls. This means that the difference in N200 and P300 latencies found between patients and controls is due mainly to the N100 latency lag (of about 25-30 msec) in the patient group, a finding previously reported by Ghiselli et al 20 . Using LORETA on magnetoencephalographic data, Larson 28 found that the cortical generators of N100, elicited by the oddball paradigm, were located in the Heschl's gyrus, where previous studies identified the tonotopic map of the human auditory cortex (for an exhaustive review, see Saenz 29 ).…”
Section: Discussionsupporting
confidence: 80%
“…The chance to study early-implanted patients with a short use of their CI coincides with the feasibility of administering a P300 paradigm to very young children. The number of EEG channels 20 does not allow for high spatial resolution. However, our results showed strong significance with regards to our specific question.…”
Section: N200 P300mentioning
confidence: 99%
“…This could be an indirect suggestion of a modulation due to the period of CI use on the brain activity linked to listening effort. Accordingly, an influence of the period of CI use in adult CI users was previously shown in an event related potential study, and specifically on the N100 amplitude and on the P300 latency [ 79 ]. Moreover, a more recent CI activation could be linked to a more sustained employment of residual low-frequency hearing [ 16 ], in particular in the non-implanted ear (that is the most of the times the ear with more residual hearing [ 80 ]), in comparison to longer period CI users, possibly resulting in a more easy fruition of music.…”
Section: Discussionmentioning
confidence: 99%